Education, Youth and Employment in Oman - Marion Breteau; Ahmed al-Suleimani (Arabian Humanities)
Aiming at providing support for youth integration into the labor market, Y is one of the first companies that have been created to strive for the participation of young people in social life in Oman. Through the description of its audience, its pedagogic programs and the relations between education and the different professional sectors of activity in Oman, this article examines the tensions and contemporary challenges that reside in “becoming an adult” in Oman.